OC-090 Quality of life and cleanliness – the key factors for patients undergoing urgent cholecystectomy. (22nd June 2015) - Parkin, E; Stott, M; Galloway, S; Welch, I; Macdonald, A
Abstract : Introduction: Ten to 15% of the population have gallstones. Surgery is the mainstay of treatment with around 60, 000 cholecystectomies being performed every year in the UK. The recent AUGIS commissioning guideline for gallstone disease lists readmission rates, day-case rates, and the proportion undergoing laparoscopic surgery as key quality specifications. In the national CholeS study, data was collected on antibiotic prophylaxis, laparoscopic versus SILS versus open, operative duration and degree of difficulty for the surgeon. But do these outcomes really matter to patients? The aim of this study was to identify a "top-5" list of factors important to patients presenting with acute gallstone disease. Method: We performed a systematic review and identified all outcomes used in surgical trials for gallstone disease in the last 5 years. We also conducted a preliminary study whereby 10 patients with gallstones were asked to document their "top 5" outcomes on a blank sheet of paper. These results were combined to produce a 41-item survey that was given to patients presenting as an emergency with gallstone pathology (excluding severe pancreatitis). Patients were surveyed on the admissions ward after reading an information leaflet and prior to surgery being performed. They were asked to score each outcome (for example, "having gallstones treated on the same admission") on a visual analogue scale of 0–100 in terms of importance to them at that time. Research and Development approval was obtained. Results: Twenty-six patients were prospectively surveyed. The median age was 46.5 years (range 21–77); 23 patients were female. Fourteen had cholecystitis, 5 had pancreatitis, 6 had biliary colic, 1 had a CBD stone. The joint top-scoring outcomes (median = 96/100) were "long-term quality of life after surgery" and "cleanliness of the ward/theatre"; followed by "standards of nursing care" (95), "pain control" and "overall satisfaction with the procedure" (both 94). The lowest scoring outcome was "being treated as a day-case" (53); followed by "stories about the hospital in local/national press" (54), "cosmetic outcome" (60), "short time before returning to normal diet" (61) and "the hospital's ranking in NHS surveys" (66). Conclusion: This pilot study has shown that for patients with acute gallstone pathology requiring cholecystectomy, the most important factors centre on cleanliness of the ward environment and long-term satisfaction and quality of life. Outcomes that surgeons perceive to be important (day-case rates, cosmesis) were actually ranked very low. When deciding upon end-points and quality metrics, future studies and guidelines need to take in to account the opinions of patients as well as those of the surgical community. Disclosure of interest: None Declared.